Generation and Characterization of Specific Antibodies to the Murine and Human Ectonucleotidase NTPDase8 - Pelletier, Julie; Salem, Mabrouka; Lecka, Joanna; Fausther, Michel; Bigonnesse, François; Sévigny, Jean (Frontiers in Pharmacology, 2017)
The ectonucleotidase nucleoside triphosphate diphosphohydrolase-8 (NTPDase8) is the last member of the E-NTPDase family to be discovered and characterized. It is a transmembrane protein which regulates the concentration of the agonists of P1 and P2 receptors at the cell surface. The functions of the enzyme are still not known partly due to the lack of specific tools such as antibodies. In this work, guinea pig polyclonal antibodies against mouse NTPDase8 and mouse monoclonal antibodies against human NTPDase8 have been generated and characterized. For the production of antibodies against mouse NTPDase8 several techniques have been tried. Several peptide antigens in several hosts (rabbit, rat, hamster and guinea pig) failed to give a positive reaction suggesting that NTPDase8 is poorly immunogenic. In this study, we describe the successful process that led to anti-mouse NTPDase8, namely the cDNA immunization technique. Monoclonal antibodies to human NTPDase8 were also obtained by cDNA immunization followed by a final injection with transfected human embryonic kidney (HEK 293T) cells expressing human NTPDase8. The specificity of these antibodies was evaluated by Western blot, immunocytochemistry, immunohistochemistry and flow cytometry. In contrast, all commercial antibodies to NTPDase8 peptides that we have tested failed to give a specific positive signal against the expressed NTPDase8 protein when used to probe Western blots. In addition, immunohistochemistry experiments confirmed the presence of NTPDase8 in mouse liver canaliculi. The tools generated in this work will help characterize NTPDase8 localization and function in future studies and its contribution to the modulation of P1 and P2 receptor activation.